«Non sufficit orbis». Mobilizing Imageries, Global Catholicism and Imperial Propaganda in the Widened Worlds of the Habsburgs in the Early Modern Age - Maria Vittoria Spissu (Intrecci d'arte, 2024)
Under Philip II, the Habsburg Empire reached across the globe a complex confederation that spanned the Atlantic Ocean and included high-tension European areas. Painters and missionaries travelled across the Catholic Monarchy, which was connected through images and cults shared across diverse geographies (the Viceroyalties of New Spain and Peru, the Mediterranean and Spanish Italy, the Spanish Netherlands and the Iberian Peninsula). Circulation of models, promotion of ideas (aimed at universal evangelization and imperialism), and the success of categories such as the Global Renaissance lead to the conception of an empire that is all-encompassing, polycentric, or even without a center. The article discusses materials and interpretative approaches, acknowledging the specificity of both contexts and agents.